Development of High-Voltage Alternating Current Measuring System - Punyavee Chaisiri; Danai Pattarakijkul; Sarawuth Pramualsingha; Peerawut Yutthagowith (My University, 2023)
This paper presents the development of a prototype reference high-voltage (HV) AC measuring system with a voltage rating of 200 kVrms and an expanded uncertainty lower than 0.4%. The developed measuring system is composed of an HV divider, a 14-bit resolution digital oscilloscope, and software for the measurement of root mean square of voltage ($V_{rms}$). The developed system was calibrated with a national reference measuring system with an expanded uncertainty of 0.2631%. The testing voltages range from 10 kVrms to 200 kVrms. It was found that the expanded uncertainties of the developed system were 0.3446% for $V_{rms}$ measurement. The developed system has expanded uncertainty at the same level as the well-known imported commercial products. In addition, compared to an import, this measuring system is significantly less expensive. This accomplishment should be used to promote the domestic HV measuring system rather than the imported one.
Keywords: Electrical and Bioimpedance Tomography; Sensor Technology and Measurement Systems; Advanced Electrical Measurement Techniques